Methylation of BDNF and SLC6A4 Gene Promoters in Brazilian Patients With Temporal Lobe Epilepsy Presenting or Not Psychiatric Comorbidities - Isabel Cristina Bandeira (Frontiers Media S.A., 2021)
The relationship between epilepsy and psychiatric comorbidities has been recognized for centuries, but its pathophysiological mechanisms are still misunderstood. It is biologically plausible that genetic or epigenetic variations in genes that codify important neurotransmitters involved in epilepsy as well as in psychiatric disorders may influence the development of the latter in patients with epilepsy. However, this possibility remains poorly investigated. The aim of this study was to evaluate the methylation profile of the BDNF and SLC6A4, two genes importantly involved in neuroplasticity, in patients with temporal lobe epilepsy (TLE) regarding the development or not of psychiatric comorbidities. One hundred and thirty-nine patients with TLE, 90 females and 45 males, were included in the study. The mean age of patients was 44.0 (+12.0) years, and mean duration of epilepsy was 25.7 (+13.3) years. The Structured Clinical Interview for DSM-IV shows that 83 patients (59.7%) had neuropsychiatric disorders and 56 (40.3%) showed no psychiatric comorbidity. Mood disorders were the most common psychiatric disorder observed, being present in 64 (46.0%) of all 139 patients. Thirty-three (23.7%) patients showed anxiety disorders, 10 (7.2%) patients showed history of psychosis and 8 (5.8%) patients showed history of alcohol//drug abuse. Considering all 139 patients, 18 (12.9%) demonstrated methylation of the promoter region of both BDNF and SLC6A4 genes. A significant decreased methylation profile was observed only in TLE patients with mood disorders when compared with TLE patients without a history of mood disorders (O.R. = 3.45; 95% C.I. = 1.08–11.11; p = 0.04). A sub-analysis showed that TLE patients with major depressive disorder mostly account for this result (O.R. = 7.20; 95% C.I. = 1.01–56.16; p = 0.042). A logistic regression analysis showed that the independent factors associated with a history of depression in our TLE patients was female sex (O.R. = 2.30; 95% C.I. = 1.02–5.18; p = 0.044), not controlled seizures (O.R. = 2.51; 95% C.I. = 1.16–5.41; p = 0.019) and decreased methylation in BDNF and SLC6A4 genes (O.R. = 5.32; 95% C.I. = 1.14–25.00; p = 0.033). Our results suggest that BDNF or SLC6A4 genes profile methylation is independently associated with depressive disorders in patients with epilepsy. Further studies are necessary to clarify these matters.